Patients with gout adhere to curative treatment if informed appropriately: proof-of-concept observational study. Issue 6 (7th June 2012) - Rees, Frances; Jenkins, Wendy; Doherty, M
Abstract : Introduction: Many doctors believe that patients with gout are unwilling to receive urate-lowering therapy (ULT) and blame them for poor adherence to management. Objective: To test the effectiveness of a complex intervention for gout that incorporates key elements of current guidelines, including full patient information, delivered in an optimal setting (specialist hospital clinic). Method: Observational study of patients reporting ongoing attacks of gout recruited from primary care lists. 106 participants (94 men, 12 women; mean age 61 years) were enrolled in the study. Patients received a predominantly nurse-delivered intervention that included education, individualised lifestyle advice and appropriate ULT. The predefined goal was to achieve serum uric acid (SUA) levels ≤360 μmol/l after 1 year in at least 70% of participants. Results: Of the 106 participants at baseline, 16% had tophi; mean (SD) baseline SUA was 456 (98) µmol/l. All participants agreed to joint aspiration to confirm gout and all wished to receive ULT. At 12 months, 92% of the 106 participants had achieved the therapeutic target (SUA≤360 µmol); 85% had SUA <300 µmol/l. Allopurinol was the most commonly used ULT, requiring a median dose of 400 mg daily to achieve the target. Improvements in Short Form-36 were observed (significant for pain) after 1 year. Conclusion: A predominantly nurse-led intervention including education, lifestyle advice and ULT can successfully achieve the recommended treatment target in more than 9 out of 10 patients. Full explanation and discussion about the nature of gout and its treatment options and individualisation of management probably account for this success.